Carbon sequestration through sustainable land management practices in arid and semiarid regions: Insights from New Mexico - Rajan Ghimire; Deb Raj Aryal; Niall P. Hanan; Sawssan Boufous; Owen Burney; O. John Idowu; Hatim M. E. Geli; Brian Hurd; Lara Prihodko (Agrosystems, Geosciences & Environment)
Abstract Arid and semiarid regions cover more than one‐third of the land surface, where the interplay between water, land use, and management strongly influences carbon (C) sequestration. Yet, information on the C management practices and how local biophysical conditions affect the C sequestration potential is limited. We explored the opportunities, research gaps, and future directions of land C sequestration in arid and semiarid regions, using New Mexico as an example. We also identified the major land use types and their potential for C storage and sequestration. Our results showed that innovations in cropland and rangeland management, protection of existing forests, and restoration of degraded forest lands after drought and wildfire enhanced C sequestration in arid and semiarid lands. Landscape‐scale C balance studies with fine‐scale mapping, improving water and nutrient use efficiency, and policy incentives to support farms will unlock the full potential of C sequestration in croplands, rangelands, and forest lands. Future research should focus on the response of land management practices to climate anomalies and their potential to sequester C and offset greenhouse gas emissions as a natural climate solution in arid and semiarid regions.